Interference of the Spectral Line Mζ in the M Energy Level Series of Ce on the F Element Kα Peak in Monazite Samples - Suwen QIU; Jinsheng HU; Guangyu SHI; Can RAO; Xiaofeng ZHANG; Wentan XU (Yankuang ceshi)
Quantitative analysis of the ultra-light element fluorine (F) has always been one of the difficulties in electron probe microanalysis (EPMA). High-resolution qualitative analysis and proper subtraction of spectral interferences from major elements are prerequisites for accurate F quantification. This study focuses on F in monazite samples with very low F content or even close to 0. Through comparison and analysis of high-resolution qualitative analysis spectra with apatite, InP, CeAl2, and LaF3 samples, it is found that the third-order line of high-content P Kα does not interfere with the F Kα peak, but the spectral line Mζ of the M energy level series of Ce interferes with the F Kα peak. Monazite with high Ce content needs accurate quantitative analysis of F through interference peak subtraction. The interference of the M-level spectral lines (including Mα, Mβ, Mζ) of rare earth elements on ultra-light element peaks needs to be taken seriously, and the necessary interference correction should be made through qualitative analysis of the spectra.